Humanizing the intensive care unit experience in a comprehensive cancer center: A patient- and family-centered improvement study. Issue 6 (December 2022) - Cuenca, John A.; Manjappachar, Nirmala; Nates, Joel; Mundie, Tiffany; Beil, Lisa; Christensen, Eric; Martin, Peyton; Diaz, Nancy; Layton, Lorraine S.; Plexman, Karen; Nates, Joseph L.; Price, Kristen J.; et al.
Abstract: Objectives: Improving family-centered outcomes is a priority in oncologic critical care. As part of the Intensive Care Unit (ICU) Patient-Centered Outcomes Research Collaborative, we implemented patient- and family-centered initiatives in a comprehensive cancer center. Methods: A multidisciplinary team was created to implement the initiatives. We instituted an open visitation policy (OVP) that revamped the use of the two-way communication boards and enhanced the waiting room experience by hosting ICU family-centered events. To assess the initiatives' effects, we carried out pre-intervention (PRE) and post-intervention (POST) family/caregiver and ICU practitioner surveys. Results: A total of 159 (PRE = 79, POST = 80) family members and 147 (PRE = 95, POST = 52) ICU practitioners participated. Regarding the decision-making process, family members felt more included (40.5% vs. 68.8%, p < 0.001) and more supported (29.1% vs. 48.8%, p = 0.011) after the implementation of the initiatives. The caregivers also felt more control over the decision-making process in the POST survey (34.2% vs. 56.3%, p = 0.005). Although 33% of the ICU staff considered OVP was beneficial for the ICU, 41% disagreed and 26% were neutral. Only half of them responded that OVP was beneficial for patients and 63% agreed that OVP was beneficial for families. Half of the practitioners agreed that OVP resulted in additional work for staff. Significance of results: Our project effectively promoted patient- and family-centered care. The families expressed satisfaction with the communication of information and the decision-making process. However, the ICU staff felt that the initiatives increased their work load. Further research is needed to understand whether making this project universal or introducing additional novel practices would significantly benefit patients admitted to the ICU and their family.